Dramatic and sustained increase in HIV-testing rates among antenatal attendees in Eastern Uganda after a policy change from voluntary counselling and testing to routine counselling and testing for HIV: a retrospective analysis of hospital records, 2002-2009 - Byamugisha, Robert; Tylleskär, Thorkild; Kagawa, Mike N.; Onyango, Saul; Karamagi, Charles A. S.; Tumwine, James K. (BMC health services research, 2010)
The burden of mother-to-child transmission of HIV in Uganda is high. The aim of this paper is to describe the experience of the first 7 years of the prevention of mother- to- child transmission of HIV (PMTCT) programme in Mbale Regional Hospital, Eastern Uganda, with particular reference to the lessons learnt in changing from voluntary counselling and testing (VCT) to routine counselling and testing (RCT) for HIV testing in antenatal services. Methods: The study was a retrospective analysis of the PMTCT records of Mbale Regional Referral Hospital, Uganda, from May 2002 to April 2009. The data on HIV testing of pregnant women and their male partners was extracted from the reports and registers using a standardized data extraction form, and data was analysed using descriptive statistics. Permission to conduct the study was obtained from School of Medicine, Makerere University College of Health Sciences; Uganda National Council of Science and Technology, and Mbale Hospital. Results: A total of 54 429 new antenatal (ANC) attendees and 469 male-partners accessed antenatal services at Mbale Regional Referral Hospital. There was a sustained, significant increase in HIV testing among new ANC attendees from 22% during the VCT period to 88% during the RCT period (p = 0.002), while among male partners, HIV testing increased from 88% to 100% (p = 0.010) However, the overall number of male partners who tested for HIV remained very low despite the change from VCT to RCT approach in HIV testing. Conclusions: Routine offer of antenatal HIV testing dramatically increased HIV testing in pregnant women and their partners in Uganda. Our findings call for further strengthening of the policy for routine HIV testing in antenatal clinics. Our study also showed that male partner HIV testing in antenatal clinics is low and this area needs further work through research and innovative interventions in order to improve male partner involvement.
Keywords: HIV-testing; Antenatal attendees; Counselling; Hospital records